The Role of the Cerebellum in Visual-Spatial Memory in Pediatric Posterior Fossa Tumor Survivors - Deviaterikova, Alena; Kasatkin, Vladimir; Malykh, Sergey (Cerebellum (London, England), 2024)
The cerebellum is involved in motor and non-motor functions. Cerebellar lesions can underlie the disruption of various executive functions. The violation of executive functions in cerebellar lesions is a serious problem, since children, after completing treatment, must return to school, finish their education, and get a profession. One of the important executive functions is working memory, which contributes to academic success. Deficits of verbal working memory in cerebellar tumors have been studied, in contrast to visual-spatial working memory. To assess this issue, 101 patients who survived cerebellar tumors and 100 healthy control subjects performed a visual-spatial working memory test. As a result, in children who survived cerebellar tumors, visual-spatial working memory is impaired compared to the control group. Moreover, with age, and hence the time since the end of treatment, the number of elements that children can retain in visual-spatial working memory increases, but still remains smaller compared to the control group. Our findings complement the idea of cerebellar involvement in visual-spatial working memory and suggest that it is disrupted by cerebellar lesions in children.